Analysis of Students’ Learning Difficulties in History Classes at Al-Khairaat Ampibabo Senior High School - Risman Risman; Lukman Nadjamuddin (Journal of Educational Sciences, 2026)
History education plays an important role in developing students’ critical thinking skills, character, and national values. However, many students still perceive History as a difficult and less engaging subject because it often requires memorizing numerous facts, such as historical figures, dates, and events. This study aims to identify and describe the learning difficulties experienced by students and to analyze the factors contributing to these difficulties in the History subject at Madrasah Aliyah Al-Khairaat Ampibabo. The research employed a qualitative descriptive approach, with data collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings revealed that students experienced difficulties in understanding materials that required extensive memorization, recalling historical figures, dates, and events, and maintaining concentration during lessons. Many students also demonstrated low interest in History because they considered the subject monotonous and overloaded with content. In addition, the midday class schedule often caused fatigue and drowsiness, while an unconducive classroom environment reduced students’ focus and participation. The study found that learning difficulties were influenced by both internal and external factors. Internal factors included low learning motivation, limited interest in the subject, and ineffective study habits. External factors consisted of limited variation in teaching methods, insufficient learning resources, and classroom conditions that did not adequately support effective learning.